Faktor Risiko Penyakit Jantung Koroner di RSI SITI Khadijah Palembang - Lily Marleni; Aria Alhabib (Politeknik Kesehatan Tanjung Karang, 2017)
In the world, the coronary heart disease is the cause of the first mortality. Based on the data from Cardiology Unit Siti Khadijah Islamic Hospital known in 2015, there is 354 sufferer of coronary heart disease, in 2016 reached for 274 patients, and in 2017 (January-March) as much as 135 patients. This research aimed to know the related to age, gender, hypertension, diabetes mellitus with the heart coronary disease Cardiology Unit Siti Khadijah Islamic Hospital Palembang in 2017. The population of the research was all of the patients with heart coronary diseases that visiting cardiology unit during January-March 2017 as much as 135 respondents. It used cross-sectional design. Data were analyzed by univariate and bivariate analysis. The result of this study got there were correlations among age (p-value=0.002), gender (p-value=0,002), hypertension (p-value=0,012), and diabetes mellitus (p-value=0,041) with the heart coronary disease Cardiology Unit Siti Khadijah Islamic Palembang in 2017. Based on to this research result suggested being done the improvement of counseling by a health worker to the coronary heart disease sufferer about the thing that related to the prevention of the coronary heart disease such as habitually and the behavior and the food pattern.